Coupled anisotropic plasticity-ductile damage: Modeling, experimental verification, and application to sheet metal forming simulation. (January 2019) - Ghorbel, O.; Mars, J.; Koubaa, S.; Wali, M.; Dammak, F.
Highlights: Fully coupled anisotropic plasticity and ductile damage models has been investigated. Non-linear isotropic/kinematic hardening is included in the model. DD13 material parameters are identified based on uniaxial tensile tests. Erichsen Cupping Test is conducted to evaluate the formability of the metal. The model can predict ductile damage growth efficiently in sheet metal forming process. Abstract: In this paper, an improved anisotropic elasto-plastic model strongly coupled with isotropic ductile damage is investigated. The quadratic Hill'48 yield criterion and non-linear isotropic/kinematic hardening are considered in the associated flow rule model. The numerical formulation of the proposed model is implemented in ABAQUS finite element code via the user material subroutines UMAT and VUMAT. The mechanical behavior of DD13 sheet metal is investigated. Its significant deep drawing capability makes this material attractive, particularly for the automotive industry. An experimental database of the DD13 mechanical properties is achieved through a serie of uniaxial tensile tests, so that the anisotropic coefficients, hardening and damage parameters are obtained. For validation purpose, the numerical results are compared to Erichsen cupping test. The combined experimental/numerical study proves the ability of the proposed model in the description of the DD13 damaged-anisotropic behavior with good accuracy. Graphical abstract: